Clostridium difficile infections in young infants: Case presentations and literature review. (2017) - Kuiper, Gé-Ann; van Prehn, Joffrey; Ang, Wim; Kneepkens, Frank; van der Schoor, Sophie; de Meij, Tim
Abstract: It has been assumed that symptomatic Clostridium difficile infections do not occur in young infants, as this specific group would lack specific C. difficile toxin receptors. As a consequence, it is often current practice not to test for C. difficile in neonates and young infants up to 2 years of age presenting with (bloody) diarrhea. The evidence to support this is, however, weak and largely based on small, poorly designed animal studies. We present two young infants with recurrent bloody diarrhea following antimicrobial therapy, positive testing for toxigenic C. difficile and successfully treated with metronidazole and vancomycin, and provide an overview of the literature on C. difficile infections in children under two years of age. Both our case histories and the literature search provide evidence for C. difficile infection as a potential cause of bloody diarrhea in neonates and young infants, in particular after previous treatment with antimicrobials.